2017
DOI: 10.1111/jar.12375
|View full text |Cite
|
Sign up to set email alerts
|

The Employers’ perspective on barriers and facilitators to employment of people with intellectual disability: A differential mixed‐method approach

Abstract: Employers' differentiated expectations and reservations towards hiring individuals with specific disabilities need to be taken into account to increase employment for people with intellectual disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…Individual (or personal) barriers include relationship and social skills difficulties [16][17][18][19]; impairments in verbal and nonverbal communication [12,20,21] and difficulty with changes in routine [15,22]. The most common external (or environmental) barriers include employer characteristics (e.g., type of business, size, location) and employment setting policies and practices [23,24]; employers' attitudes and misconceptions [12,13,[24][25][26][27][28]; work setting [12]; perceived costs of accommodation [23,29,30]; low family expectations [17,31] and stigma [32,33]. Much of this work on barriers is descriptive in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual (or personal) barriers include relationship and social skills difficulties [16][17][18][19]; impairments in verbal and nonverbal communication [12,20,21] and difficulty with changes in routine [15,22]. The most common external (or environmental) barriers include employer characteristics (e.g., type of business, size, location) and employment setting policies and practices [23,24]; employers' attitudes and misconceptions [12,13,[24][25][26][27][28]; work setting [12]; perceived costs of accommodation [23,29,30]; low family expectations [17,31] and stigma [32,33]. Much of this work on barriers is descriptive in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies to date have employed a multi-stakeholder qualitative approach. Most of the previous research on employment for persons with developmental disabilities has been driven by survey or population data [e.g., 9,27,[36][37][38][39][40][41] or from the perspective of a single stakeholder group [24,27,[42][43][44]. A better understanding of barriers relative to persons with developmental disabilities and employment from the multiple perspectives of a diverse group of stakeholders helps to inform future policies in the area of inclusive employment as well as to aid direct efforts to create more appropriate supports and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous research on employment for PWDD has been driven by survey or population data e.g. [1,[69][70][71][72][73][74][75] or from the perspective of a single stakeholder group [70,[76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…The main cause identified is the employers' attitude towards hiring disabled person. Employers have a negative perception towards person with disabilities whereby they are concerned that person with disabilities could not perform the task (19)(20)(21)(22). Past literature shows that attitude of managers impact the hiring of PWDs (23)(24)(25) found that attitude influences intention, while in turn, intention predicts behaviour.…”
Section: Employers' Attitudementioning
confidence: 99%
“…They are concerned about co-workers attitudes towards person with disabilities (33) and the ability of their supervisors in managing person with disabilities (20). It is also evident from the literature that employers fear of legal liability (22,27).…”
Section: Employers' Attitudementioning
confidence: 99%